Less Polar Compounds and Targeted Antioxidant Potential (In Vitro and In Vivo) of Codium adhaerens C. Agardh 1822 - Sanja Radman; Ana-Marija Cikoš; Ivana Flanjak; Sanja Babić; Lara Čižmek; Drago Šubarić; Rozelindra Čož-Rakovac; Stela Jokić; Igor Jerković (MDPI AG, 2021)
Codium adhaerens from the Adriatic Sea (Croatia) was comprehensively investigated regarding less polar compounds for the first time. Although there are several phytochemical studies on C. adhaerens from other regions, this is the first report on volatile organic compounds (VOCs) from fresh (FrCa) and air-dried (DrCa) samples. The novelty is also related to its targeted antioxidant potential in vitro and in vivo. The main aims were to: (a) identify and compare VOCs of FrCa and DrCa obtained by headspace solid-phase microextraction (HS-SPME) and hydrodistillation (HD); (b) determine fatty acid (FA) composition of freeze-dried sample (FdCa); (c) determine the composition of less polar fractions of FdCa by high-performance liquid chromatography-high-resolution mass spectrometry with electrospray ionisation (UHPLC-ESI-HRMS); and (d) comprehensively evaluate the antioxidant activity of the fractions by four in vitro assays and in vivo zebrafish model (including embryotoxicity). Significant changes of VOCs were found after air drying. ω6 FAs were present in higher content than ω3 FAs indicating C. adhaerens as a good source of dietary polyunsaturated FAs. The results obtained in vivo correlate well with in vitro methods and both fractions exerted similar antioxidative responses which is in agreement with the high abundance of present biomolecules with known antioxidant properties (e.g., fucoxanthin, pheophytin a, and pheophorbide a). These results suggest that C. adhaerens might be a potent source of natural antioxidants that could be further used in the research of oxidative stress-related diseases.